Músicas que ultrapassam as estruturas regidas por números : uma análise de práticas matemáticas em construções de instrumentos musicais - Camargos, Chrisley Bruno Ribeiro (2017)
The aim of this research is to show how the practices expressed in the relations, discussions and the scenarios of musical instrument constructions are not restricted to a mathematical practice that can be considered scholarly or academic; thus, such mathematics will be discussed from the perspective of the situated practices. This work is a qualitative approach field research which presents an ethnography bias, because it is a work in which the researcher spent about two years in a Music Course, following from within the classes and musical practices. The data produced refer mainly to: the researcher's field journal, related to the subjects of the Music Course of a public university; questionnaires applied to students; to the teacher's written observations of the field journal notes; the videos made in the presentations of some classes and the reports of the students that were made available by the professor of the courses. The courses analyzed involve creation and experimentation of musical instruments and they were observed during the year 2015. As a theoretical basis for the discussions and analyzes of the data produced, theories concerning the Wittgensteinian philosophy, as well as notions about social practices and situated practices described by the authors Lave and Wenger were used. As a context for arguments about the theoretical musical aspect, ideas related to authors about a contemporary and experimental type of music that is not limited to a system pertinent to a dialectic of heights and chronometric times were used. It is considered that experimental music would be a cultural form, in which the paths and scenarios are designed and by which the participants create their instruments. Through the analyzes and discussions raised, taking into consideration the theoretical aspects studied and described, it was verified that, among the several types of mathematical practices observed, some can be considered within the limits of academic or school mathematics, especially in other situations, the activity scenarios outline new ways in which apprentices or young masters are concerned with instrumental sounds, with the material / visual forms, or with the musical system they intend to create. In this way, the observed mathematics begins to participate in a new game, which requires approximations, which requires musical knowledge; the "exactly like this" gives way to forms of approximation, and, at certain moments, mathematics is abandoned and give way to what some musicians call ways of perception. This allows us to affirm that in the observed practices in which aspects related to experimental music are established, the structures imposed by the mathematical model of the same temperament or musical notation score have become a "slippery ice", for which, however, it was necessary to walk on.